HUBUNGAN ANTARA KUALITAS PELAYANAN DENGAN TINGKAT KEPUASAN MASYARAKAT (Studi kasus pembuatan e-KTP di Kecamatan Sumberrejo Kabupaten Bojonegoro) - Istiqomah, Dian Aulatul (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
The Relationship Between The Quality Of Service With The Level Of Satisfaction. Public services essentially serve the community with a predetermined service standard for the recipient to be satisfied. In reality, however, problems are often encountered causing delay in the process of making e-ID cards. In this research problem formulation is as follows first what is relation between service quality with level of society satisfaction? And the second what are the factors that inhibit e-ID card service at Sumberrejo District Office of Bojonegoro Regency? The research focus on this research consists of 6 dimensions, namely: reliability, responsiveness, assurance, empathy, tangibles, and complaints handling service. The type of this research is descriptive qualitative with data collection technique interview, observation, and documentation. Data analysis technique used is qualitative analysis. The results of this study can be concluded that from 6 dimensions above the highest level of quality is the handling of complaints suggestions and inputs while the lowest is the empathy dimension. For the satisfaction of the society from the highest dimension is on handling complaints suggestions and inputs while the lowest is on the dimensions of reliability. Â Keywords: Service Quality, Public Satisfaction